A study of obstetric and fetal outcome of placenta previa in scarred and unscarred uterus - Nair, Rema V.; Sri S., Raagavi; Ponmalar, Jameela (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: This study was conducted to study the maternal and fetal outcome in case of placenta previa in a scarred and unscarred uterus. Methods: This was 10 months’ prospective study conducted in Sree Mookambika Institute of Medical Science, Kulasekharam in the year between January 2021 to October 2021, among the cases of placenta previa with scarred and unscarred uterus. During the study period out of 1882 deliveries 20 cases of placenta previa beyond 28 weeks of gestation were reported. These cases were divided into two groups, scarred uterus (group A) and unscarred uterus (group B). Results: Incidence of placenta previa in scarred uterus (A) was higher than in unscarred uterus (B). Postpartum haemorrhage was seen in 25% of cases malpresentation was found in 55% of cases among which 5 cases in scarred group and in 6 cases in unscarred. Caesarean hysterectomy was performed in 1 case in scarred uterus. Neonatal intensive care unit was required for 15% of babies born to mother with placenta previa. Conclusions: The risk of placenta previa increases with increase in number of previous caesarean section, increased parity and advanced maternal age. Postpartum hemorrhage and blood transfusion are not uncommon in both group. Planned management at a tertiary care centre is obligatory. Mode of delivery is by emergency LSCS in case of bleeding per vaginum or elective LSCS.